PROBLEMS OF INSTITUTIONS' INTERACTION: VALUE OF A SERVICE AS A SPECIAL FORM OF COMMODITY (LOGISTIC APPROACH) - Skorobogatova, T.; Burkaltseva, D.; Lunyakov, O.; Niyazbekova, Sh.; Guk, O.; Korotkevich, E.; Goigova, M. (Scientific Journal of Pedagogy and Economics, 2020)
The concept of value is highly versatile. They distinguish economic, social, political, aesthetic, spiritual, and other values. The purpose of the study is to consider the value as a scientific category, to be exact, consider the value of services as a special form of commodities, using a logistics approach, to define the terms and concepts in the dictionary, based on the economic institutions' interaction problems.